Tonga : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2001)
This report analyzes the recent economic developments of Tonga by assessing the potential output, prices, employments, production by sectors, and private sector development policy. The paper describes the public finance, budgetary process and structure of the budget, public enterprises, and privatization. The paper reviews the banking supervision and bank soundness, money and credit development, and monetary policy objective of the national reserve bank of Tonga. The study also provides the details of the foreign reserves and exchange rate, current transfers, capital account, and debt of the country.